Accuracy and safety of freehand vs. end-on fluoroscopic guided drill-hole placement in canine cadaveric thoracic, lumbar and sacral vertebrae - Driver, Colin J.; Nores, Victor Alves; Thatcher, Heidi; Navarro-Carrillo, Maria; Rose, Jeremy (Frontiers in Veterinary Science, 2024)
Objective: To develop and evaluate the safety and accuracy of an open, end-on fluoroscopic guided (EOFG) drill hole position technique in canine cadaveric spinal surgery, in comparison to a traditional free-hand (FH) drilling technique.Animals: Canine cadaveric vertebral columns (n = 4).Computed tomography (CT) scans were performed for in-silico planning. Ideal implant purchase depth and angulations were determined from previously published data. Plans for end-on fluoroscopic guided drill holes included angled reconstructions in thick slab mode to mimic fluoroscopic images. Following surgical preparation of T8 to S2, holes were drilled by one of two experienced surgeons randomised evenly by operated side, surgeon, and technique. C-arm fluoroscopy was utilised for the end-on technique. CT was repeated after the procedures. Safety was determined categorically using a modified Zdichavsky classification and 'optimal' placement was compared between techniques. Continuous data for drill-hole accuracy was calculated as angle and depth deviations from the planned trajectories. Data sets were analyzed at both univariable and multivariable levels with logistic regression analysis.Results: Drill hole safety was categorised as optimal (modified Zdichavsky classification 1) in 51/60 (85%) of drill holes using EOFG and 33/60 (55%) using FH (P < 0.001) techniques. There were no 'unsafe' holes (modified Zdichavsky classification 3a). Optimal drill hole placement was significantly associated with the EOFG technique and use of the largest cadaver, and was significantly less likely within the thoracic region. Mean angle and depth deviations were significantly lower with the EOFG technique. Angle deviations were significantly lower for EOFG in the lumbar region, whereas bone purchase deviations were significantly lower for EOFG in both the thoracic and lumbar regions. The mean time taken to drill the hole was significantly longer for the EOFG technique.Optimal drill hole placement was significantly more likely with the EOFG technique and improved the accuracy of bone purchase in the thoracic region. Clinical significance: The EOFG technique shows promise for translation into a clinically setting, potentially improving implant purchase and therefore stabilizing construct strength, whilst potentially reducing the likelihood of neurovascular injury and need for surgical revision.